Art, Ideology and Scientific Knowledge: Louis Althusser’s Philosophical Approach to the Film Analysis: The Battle of Algiers 1966 - Damouche , Ouahiba (Dirasat: Human and Social Sciences, 2024)
Objectives: This study discusses the historical accuracy of the film and its portrayal of the battle of Algiers far away from the European and western egocentralism, evaluating the scenes and images and their non-leanear narrative structure and effectiveness in capturing different ideological perspectives when compared to documentary footage and factual depictions, in order to create a sense of objectivity and realism. Methods: Philosophical analysis is used through constructing and deconstructing concepts of the film. Louis Althusser’s theory of ideology is applied in this research paper to better comprehend how ideology affects the dynamics of power and social institutions. Additionally, the recorded records from the archives of the liberation of Algeria are utilised. Results: Althusser’s notion of social formation, as a construction, is presented as a construction emerging from roles and central positions. This moving away from the egocentric vision , with no regulating concept, no starting seed, no united whole contradicted to the use of ideology as seeking for completion and wholeness. In brief, despite attempts to utilize what they claim to be scientific knowledge, the endeavor to harness these possibilities led to new technological and scientific analysis. However, its utilization within the framework of state apparatus ideology and social formation bifurcated the film into two levels: film analysis and post-film analysis. Conclusions: linking science to art has become established by means of linking both reality and philosophical fiction. So the distinction between the concepts of science and meta- science, art and meta- art, ideology and meta-ideology became necessary.